Sex and Age-Group Differences in Strength, Jump, Speed, Flexibility, and Endurance Performances of Swedish Elite Gymnasts Competing in TeamGym - Höög, Stefan; Andersson, Erik P. (Frontiers in Sports and Active Living, 2021)
Purpose: To analyze sex and age group differences in strength, jump, speed, flexibility, and endurance performances of TeamGym athletes. Methods: A total of 91 Swedish elite gymnasts (junior female, n = 26, age = 15.4 y; senior female, n = 23, age = 20.0 y; junior male, n = 19, age = 15.6 y; senior male, n = 23, age = 20.6 y) participated in three testing sessions on three separate days. These were: (1) a series of flexibility tests for the lower- and upper-body; (2) strength tests for the lower- and upper-body; and (3) various types of jumps, a 20-m sprint-run, and a 3000-m run test. Results: Males were 24% stronger in the back squat one-repetition maximum (relative to body mass) compared to females (P<0.001, Hg=1.35). In the pull-ups and dips, 2.4 and 2.3 times more repetitions were completed by the males compared to the females (both P<0.001, 0.70≤R≤0.77). However, females were similarly strong as males in the hanging sit-ups test (P=0.724). The males jumped 29%, 34%, 33%, and 17% higher in the squat jump (SJ), countermovement jump (CMJ), countermovement jump with arm swing (CMJa), and drop jump (DJ), respectively, compared to the females (all P≤0.002, 0.14≤ηp2≤0.60). In the 20-m sprint run, males were 4% faster than females (P<0.001, R=0.40). Moreover, the females had significantly better flexibility than the males in the trunk forward bending, front split, and side split tests (all P<0.001, 0.24≤ηp2≤0.54). In the 3000-m run test, males were 11% faster than females (P<0.001, ηp2≤0.54). Compared to junior athletes, seniors performed better in the pull-ups, dips, SJ, CMJ, CMJa, and 20-m sprint-run tests (all P≤0.012, 0.31≤R≤0.56, 0.16≤ηp2≤0.25), with separate within-sex age-group differences (i.e., juniors versus seniors) that were significant for the males but not for the females in the SJ, CMJ, CMJa, and 20-m sprint-run tests (males: all P<0.001, 0.67≤R≤0.69, 1.37≤Hg≤2.01; females: all P=0.298-732). Conclusions: Large sex and age-group differences were observed for most physical performance metrics with specific within-sex age-group differences only observed for male athletes, with male seniors performing better than juniors in the SJ, CMJ, CMJa, and 20-m sprint-run tests.